1991
DOI: 10.1210/jcem-72-4-768
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Extracellular Volume and Suppression of Atrial Natriuretic Peptide after Growth Hormone Administration in Normal Man

Abstract: Sodium retention and symptoms and signs of fluid retention are commonly recorded during GH administration in both GH-deficient patients and normal subjects. Most reports have however, been casuistic or uncontrolled. In a randomized double blind placebo-controlled cross-over study we therefore examined the effect of 14-day GH administration (12 IU sc at 2000 h) on plasma volume, extracellular volume (ECV), atrial natriuretic peptide (ANP), arginine vasopressin, and the renin angiotensin system in eight healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 33 publications
4
67
1
1
Order By: Relevance
“…However, DEXA cannot distinguish between body cell mass and water and consequently these data may not be accurate since GHT is associated with an increase in the intracellular water component [37]. Computed tomography and MRI are two of the most sensitive methods that could lead to a reliable estimate of visceral fat, but both procedures require expensive specialized equipment and in this light the VAI is a clinical index derived from MRI-based studies and represents a better indicator of adipose dysfunction [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, DEXA cannot distinguish between body cell mass and water and consequently these data may not be accurate since GHT is associated with an increase in the intracellular water component [37]. Computed tomography and MRI are two of the most sensitive methods that could lead to a reliable estimate of visceral fat, but both procedures require expensive specialized equipment and in this light the VAI is a clinical index derived from MRI-based studies and represents a better indicator of adipose dysfunction [17].…”
Section: Discussionmentioning
confidence: 99%
“…In both groups of patients, body¯uid is normalized after, respectively, GH treatment and surgical treatment of the hypophysis. In healthy men, the pharmacological administration of GH also raises body-¯uid volume (2). The action of GH is thought to be mediated by aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation is the potential that some of the changes in skeletal muscle mass are secondary to changes in ECW. Previously it has been demonstrated that both short-and long-term administration of GH increases ECW (39,40). Testosterone also increases ECW, an effect amplified when co-administered with GH (41).…”
Section: Discussionmentioning
confidence: 97%